Pengaruh Pupuk Hayati dan Azolla (Azolla pinnata) terhadap Beberapa Sifat Kimia Tanah, Pertumbuhan, dan Hasil Padi Sawah (Oryza sativa L.) - Setiawati, Mieke Rochimi; Ilyas, Ichsan; Suryatmana, Pujawati; Setiawan, Ade (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2023)
Application of Biofertilizer and Azolla (Azolla pinnata) to Improve Several Soil Chemical Properties, Growth and Yield of Rice Plants (Oryza sativa L.). Efforts to increase agricultural production through intensification programs cannot be separated from using artificial chemical fertilizers. However, the continuous use of artificial chemical fertilizers must be balanced by providing organic matter to avoid a deficiency of land-available nutrients, organic matter, and beneficial microorganisms. Using biofertilizers and Azolla can help provide nutrients and improve the biological properties of the soil. This research aimed to determine the effect of the interaction of biofertilizer and Azolla in increasing soil N and lowland rice yields. This research was conducted in a greenhouse, experimental garden, Ciparanje, Jatinangor, Faculty of Agriculture, Universitas Padjadjaran. The experimental design used was a factorial randomized block design with two factors. The first factor, the dose of Azolla pinnata (A), consisted of 4 levels: without Azolla, Azolla 10 t ha-1, Azolla 20 t ha-1, and Azolla 30 t ha-1. In comparison, the second was the dose of solid biofertilizer (H), which consisted of 3 levels, without biofertilizer, 12.5 kg ha-1 biofertilizer, and 25 kg ha-1 biofertilizer, repeated three times. The results of the study showed that there was no interaction between biofertilizer and A. pinata on total soil N, plant N concentration, soil C/N ratio, and lowland rice (Oryza sativa L.) yields; however, the application of Azolla 30 t ha-1 increase the number of productive tillers. The application of biofertilizer and Azolla has yet to increase rice plants' Dry Harvested Grain (DHG). However, the DHG tends to increase by 9.58% and 9.95%, respectively, compared to the control